Buffalo Soldiers - Alexander M. Bielakowski (Symphony in the Flint Hills, 2013)
The period from the end of the Civil War until the entry of the United States into World War I was almost a “golden era” for African-Americans in the US military. For the first time, African-Americans could serve in the regular military in peacetime.
Keywords: Buffalo Soldiers; black; African American; rights; war; Civil War; military; army; Ft. Riley; 9th Cavalry; 10th Cavalry; Alonzo Scott; Jim Crow; peacetime; peace; freedom; 24th Infantry; 25th Infantry; regiments; West Point; Henry O. Flipper; John H. Alexander; Charles Young; Indians; Native Americans; honor; duty; W. B. Barnes; Flint Hills; mystery; legend; story; Medal of Honor; Sergeant Hamilton; World War II; World War I; Indian Wars; Spanish-American War; Philippines; civil rights; injustice